2011
DOI: 10.1017/jfm.2011.34
|View full text |Cite
|
Sign up to set email alerts
|

Control of laminar separation using pulsed vortex generator jets: direct numerical simulations

Abstract: Direct numerical simulations (DNS) are employed to investigate laminar boundary layer separation and its control by pulsed vortex generator jets (VGJs), i.e. by injecting fluid into the flow through a spanwise array of small holes. Particular focus is directed towards identifying the relevant physical mechanisms associated with VGJ control of low-Reynolds-number separation, as encountered in low-pressure turbine applications. Pulsed VGJs are shown to be much more effective than steady VGJs when the same moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Figure 21(b,d,f,h,j,l,n,p), on the other hand, shows a process of periodic merging and shedding of vortices with an increase in the concentrated vorticity within. The dynamic behaviour of the separation bubble depicted in figure 21 is very similar to that observed by Pauley et al (1990), and Postl et al (2011). Figure 22 shows the phase-averaged flow field over the airfoil with plasma control at α = 6…”
Section: Dynamics Of Separation Bubblessupporting
confidence: 68%
See 1 more Smart Citation
“…Figure 21(b,d,f,h,j,l,n,p), on the other hand, shows a process of periodic merging and shedding of vortices with an increase in the concentrated vorticity within. The dynamic behaviour of the separation bubble depicted in figure 21 is very similar to that observed by Pauley et al (1990), and Postl et al (2011). Figure 22 shows the phase-averaged flow field over the airfoil with plasma control at α = 6…”
Section: Dynamics Of Separation Bubblessupporting
confidence: 68%
“…The resultant mean flow change upstream of the transition location led to a reduction in the size of the separation regions as well as a stabilization of the flow. Rist & Augustin (2006) and Postl, Balzer & Fasel (2011) carried out flow separation control using instability waves and vortex generator jets, respectively, and they concluded that unsteady forcing was more effective than steady forcing in controlling laminar separation bubbles. When unsteady forcing was applied to the flow at the naturally unstable frequency of the separated shear layer, instability modes developed into large-scale spanwise coherent structures, initiating a necessary entrainment of high-momentum fluid to reattach the flow (Postl et al 2011).…”
Section: Flow Separation Controlmentioning
confidence: 99%
“…Separation is alleviated through the mechanism of energizing the flow in the boundary layer, either by directly injecting high-momentum fluid through blowing or by introducing high-momentum fluid from the exterior cross-flow through suction. The pulsed jet [10][11][12][13] is similar to the steady blowing but differs in that the jet is injected into the boundary layer periodically. The boundary layer flow is sufficiently excited that perturbations amplify and transition to turbulence is initiated.…”
Section: Introductionmentioning
confidence: 99%
“…Year Type Application Reynolds Number Advantage(s) [57] 2017 Microjet Wind turbine 1,000,000 Increased pressure coefficient [57] 2017 Microjet Wind turbine 1,000,000 Increased lift [58] 2017 VGJ Low-pressure turbine 50,000-300,000 Max 75% reduction in total pressure loss [9] 2016 VGJ, deflected TE Low pressure turbine 20,000; 50,000 12.5% reduction in solidity [23] 2016 VGJ, steady Gas turbines 840,000 Reduced corner vortices, 14% reduction in total pressure loss [59] 2014 Microjet Wind turbine 1,000,000 Increased lift [60] 2013 Microjet Low pressure turbine 50,000 Max 85% reduction in wake-loss coefficient [12] 2013 Pulsating jet Stemme S10 motor glider 1,750,000 30% increase in lift-to-drag ratio [61] 2012 VGJ, unsteady Low pressure turbine 25,000; 50,000 Separation control [62] 2011 VGJ, unsteady Low pressure turbine Induced reattachment [63] 2011 VGJ, unsteady Low pressure turbine 25,000; 50,000 Separation control, increased lift, reduced total pressure loss [64] 2009 VGJ, unsteady Airfoil SS 7700 (Re θ ) Delayed separation [65] 2004 VGJ, steady Low pressure turbine 25,000 Max 50% reduction in total pressure loss [65] 2004 VGJ, unsteady Low pressure turbine 25,000 Max 40-50% reduction in total pressure loss Outcome: Controlled separation, induced reattachment Nowadays, the SDBDAs are used more than the SCDAs since they provide more stable discharge [15], and AC operation results in lower voltage requirement [18] and low power consumption (order of watts) [66]. On the other hand, the SDBDA may suffer from high peaks of electric input power under certain conditions; however, this may be reduced by using inductive filters between the power supply and the actuator [15].…”
Section: Refmentioning
confidence: 99%
“…The most important design parameters of vortex generator jets are injected mass flow rate, jet location and pulsating frequency [74]. Vortex generator jets operating in unsteady (pulsed) operating conditions are more efficient than steady ones due to the reduced injected mass flow rate [62,65]. Kostas et al [64] found that a counter-rotating configuration for a vortex generator jet (which consists of two jets pointing to opposite directions and results in counter-rotating streamwise vortices into the boundary layer) is more effective than a co-rotating one (which consists of individual jets pointing to same direction and results in co-rotating streamwise vortices), since it requires less injected mass flow.…”
Section: Refmentioning
confidence: 99%